Social and Cultural Influences on Management for Carbon Sequestration on US Family Forestlands: A Literature Synthesis - A. Paige Fischer; Susan Charnley (International Journal of Forestry Research)
Nonindustrial private—or “family”—forests hold great potential for sequestering carbon and have received much attention in discussions about forestry-based climate change mitigation. However, little is known about social and cultural influences on owners' willingness to manage for carbon and respond to policies designed to encourage carbon-oriented management. We review the published literature to examine how family forest owners' values, ecological knowledge, risk perceptions, and forest management and policy preferences may affect their interest in managing for carbon sequestration. We find that although family forest owners may not be particularly motivated to mitigate climate change, their forest management values and practices compliment many carbon-oriented management strategies. However, the strong value owners place on privacy and autonomy, and the weak importance many place on financial reward, may inhibit participation in policies and programs that incentivize carbon-oriented management. These findings also have implications for policy efforts to encourage management for other ecological values besides carbon sequestration on family forestlands.